The Relevancy of Religious Literacy in Social Studies Curricula: Quebec’s CCQ as a Case Study - Chan, W. Y. Alice‏ (Religions, 2024)
This article explores Quebec’s recent transition from the “Ethics and Religious Culture” (ERC) program to the “Culture and Citizenship in Quebec” (CCQ) program, emphasizing the role of religious literacy in secular societies. We investigate the rationale behind the shift, and examine the ERC’s focus on fostering understanding of diverse religious and ethical perspectives as well as CCQ’s broader mandate to integrate cultural and civic education and its aim at the development of a shared and common public Quebecois culture. The case study highlights the pedagogical and societal implications of this change, discussing how the CCQ program aims to enhance civic engagement, cultural awareness, and social cohesion. Furthermore, the article identifies opportunities for educators to address pressing global challenges, such as polarization, reconciliation, and the climate crisis, within the new curriculum framework. By promoting critical thinking, inclusivity, and active citizenship, fostering religious literacy in such programs presents a unique opportunity for educators and youth to contribute to a more resilient and harmonious society.